Transforming Painting to IdeaConceptual Art: Between Self-Expression and the Problem of the Uncollectible (Al-Academy, 2025)
AbstractThis research explores the essential shift in modern art from material forms (such as paintings) to "concepts" as the essence of artistic creation, focusing on conceptual art and the dilemma of its non-collectible nature. The first section examines the complex relationship between art and the market, highlighting how conceptual art resists commodification through ephemeral works, like Cattelan’s banana piece, which sparked philosophical debates on artistic value. The second section analyzes installation art as the most expressive medium of conceptual practices, emphasizing immersive, sensory experiences over traditional visual display. The third section investigates the historical and intellectual motivations behind conceptual art, tracing its roots to socio-political upheavals and the influence of poststructuralist thought. The research concludes by outlining a classification of conceptual art types, including linguistic, procedural, performative, institutional critique, and documentary art. Ultimately, the study affirms that conceptual art does not offer fixed answers, but provokes critical thinking, restoring the role of aesthetic experience as a free and reflective act that challenges market-driven definitions of art.